Description of ST Segments Elevation of Myocardial Infarction on Patients Undergoing Primary Percutaneous Coronary Intervention in dr. M. Djamil Hospital Padang - Permatasari, Pradita Diah; Fadil, Muhammad; Syafri, Masrul (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
Myocardial infarction is influenced by various risk factors consist of gender, age, family history, smoking, hypertension, dyslipidemia, diabetes mellitus and menopause. The aim of this study was to describe the description of sex, age and risk factors possessed by patients with ST segments Elevation Myocardial Infarction (STEMI) who underwent primary percutaneous coronary intervention (PPCI) procedures at Dr. M. Djamil hospital Padang. Amount of 40 people were obtained specifically for STEMI patients who underwent PPCI and were treated at the integrated heart services installation of RSUP dr. M. Djamil Padang from July-September 2019. The research variables measured were age, sex, risk factors for hypertension, diabetes mellitus, smokers, dyslipidemia, family history and menopause. Data was analyzed in the form of univariate analysis, which explained each research variable according to the proportion and frequency values. The results were found in 40 patients with acute ST segments elevation myocardial infarction, all aged > 40 years, most were male (85%) and the most risk factor was smoking (82,5%). We conclude that STEMI patients who underwent PPCI in dr.M. Djamil hospital Padang from July-September 2019 were all > 40 years old, most were male, with the most risk factors were smokers.